APPLICATION OF INFORMATION TECHNOLOGY TO ANALYZE THE STRATEGIES USED FOR FORMATION OF VALUES - Morales, Griselda Cortes; Valdez, José Luis Cendejas (European Scientific Journal, ESJ, 2015)
The research has been developed with the objective to provide an analysis of the values education strategies used by teachers in public high schools at Monclova, Coahuila, México; to promote formation of values in their students. Participants were a total of 131 teachers of both sexes chosen randomly from seven different public high schools, with ages ranging between 21 and 65 years. Through field research and descriptive documentary, it was found that the strategies used by teachers are: selfregulation of behavior and values clarification. To conclude, any attempt to values education will only succeed if it does occur under certain conditions as an open dialogue climate, an appropriate methodology and most importantly, the teacher must estimate values, feel them, practice them, and have the desire above all of transmitting them.